(untitled) (International Journal of Interreligious and Intercultural Studies, 2024)
The teachings of Shiva-Buddhism are a beautiful fusion of Hinduism and Buddhism, not just a legacy of the past, but a living religion that is practiced by many Balinese people. Pura Dalem Sakenan is an example of this syncretism. The temple’s main shrine, called the candi or gedong sekar kancing gelung, stands as a symbol of syncretism. It is a combination of the padmasana, a Hindu altar, with a Buddhist-style temple structure. Pura Dalem Sakenan is not just a holy place. It is a center of spiritual life, where ?iwa-Buddha rituals and practices take place. The faithful gather to pray, make offerings, and perform traditional ceremonies that are rich in Hindu-Buddhist nuances. Pura Dalem Sakenan as one of its cultural gems, invites us to open our eyes and hearts to the beauty of diversity. On this island, Hinduism and Buddhism are not two separate entities, but two sides of the same coin, complementing each other and forming a unique spiritual story.